Double-fluxing-agent modified single-crystal nickel-iron-manganese-based positive electrode material as well as preparation method and application thereof

By doping B3+ and Sr2+ ions into the positive electrode material of sodium ion battery, a double flux modified single crystal nickel-ferromanganese-based positive electrode material is solved, and the problem of stress accumulation in the charge and discharge process of O3 type nickel-manganate is improved. The cycle stability and specific capacity are achieved to achieve efficient sodium ion battery performance.

CN119181778APending Publication Date: 2024-12-24HUNAN NANENG TIMES TECH DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311687067.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-08
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

During the charging and discharging process of the existing O3 type sodium nickel manganate, the accumulation of internal stress of the material due to repeated de-embedding of sodium ions, resulting in rapid decline in capacity, low energy density and short cycle life. The existing doping method has limited effect.

Method used

A single crystal nickel ferromanganese-based positive electrode material is modified using a dual flux. By doping B3+ and Sr2+ ions in the sodium layer and the transition metal layer, a single crystal structure is formed to improve the cyclic stability and specific capacity of the material.

Benefits of technology

In the voltage range of 2-4.0V, the discharge specific capacity of the material reaches 138.24mAh g-1, the capacity retention rate of 50 cycles reaches 90.83%, and the preparation method is simple and easy to operate, suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181778A_ABST
    Figure CN119181778A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of battery materials, and particularly relates to a double-fluxing-agent modified single-crystal nickel-iron-manganese-based positive electrode material as well as a preparation method and application thereof. The chemical formula of the single-crystal nickel-iron-manganese-based positive electrode material is [Na1-2zSrz] (NiaFebMncMd) 1-yByO2, M is one or more of Mg, Al, Ti, Zn, Zr, Cu, Nb, W and Mo, y is greater than 0 and less than or equal to 0.1, z is greater than 0 and less than or equal to 0.05, values of a, b, c and d depend on charge balance, B < 3 + > is doped in octahedral vacancies of the transition metal layer, and Sr < 2 + > is doped into the sodium layer. The positive electrode material presents a single crystal morphology and has excellent cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery materials, and in particular relates to a double flux modified single crystal nickel-iron-manganese based positive electrode material and a preparation method and application thereof. Background Art

[0002] With the growing demand for electronic devices and electric vehicles, lithium-ion batteries have been widely used as important energy storage devices. However, due to the shortage, high cost and uneven distribution of lithium resources, while sodium resources are abundant, easy to obtain and low cost, sodium-ion battery technology has developed rapidly, and the industrialization process in the fields of energy storage and small power is also advancing rapidly.

[0003] Positive electrode materials are the core components of batteries. Currently, positive electrode materials for sodium-ion batteries can be divided into layered oxides, Prussian blue and polyanions. Among them, layered transition metal oxide positive electrode materials have high energy density and compaction density, and have a similar synthesis route to lithium battery ternary materials. They are considered to be more ideal positive electrode materials for sodium-ion batteries. Layered transition metal oxide materials for sodium-ion batteries can be divided into P2, O3 and other crystal forms. Compared with P2 materials, O3 materials have the advantages of higher initial sodium content and high capacity. However, due to the complex phase transition and slow kinetics during the charging and discharging process, the capacity of O3 layered transition metal oxide materials decreases rapidly and the energy density is low. Among them, the O3 type sodium nickel manganese oxide positive electrode material accumulates internal stress in the material during the charging process due to repeated sodium ion deintercalation, secondary particles crack along the grain boundaries, and the contact interface between the material and the electrolyte increases, thereby aggravating the interface side reaction, resulting in serious gas production problems during the battery cycle, and greatly reducing the battery cycle life and safety. In order to improve its cycle life, element doping is mainly used at this stage, such as Na, transition metal and oxygen doping, but the doping effect is limited. For example, although high doping levels can significantly improve stability, the capacity loss is too excessive. Summary of the invention

[0004] In order to overcome the problems in the prior art, the present invention provides a double flux modified single crystal nickel-iron-manganese based positive electrode material and a preparation method thereof, a positive electrode plate and a sodium ion battery. The prepared positive electrode material is a single crystal particle with excellent cycle stability and high specific capacity.

[0005] In an embodiment of the present invention, the present invention proposes a double flux modified single crystal nickel iron manganese based positive electrode material, the chemical formula of the single crystal nickel iron manganese based positive electrode material is: [Na 1-2z Sr z ](Ni a Fe b Mn c M d ) 1-y By O 2 , where M is one or more of Mg, Al, Ti, Zn, Zr, Cu, Nb, W, and Mo, 0<y≤0.1, 0<z≤0.05, and the values ​​of a, b, c, and d depend on the charge balance.

[0006] In one embodiment, the single crystal nickel-iron-manganese-based positive electrode material is an irregular polyhedron, the particles are evenly dispersed, and the particle size is 2 to 5 μm; in the crystal structure of the double flux modified single crystal nickel-iron-manganese-based positive electrode material, the sodium layer spacing is The interlayer spacing of transition metal oxides is

[0007] In one embodiment, the metal ions in the solvent are doped into the sodium sites of the sodium layer of the nickel-iron-manganese positive electrode material and the octahedral vacancies between the transition metal layers thereof.

[0008] Based on the same technical concept, the present invention also provides a method for preparing the above-mentioned double flux modified single crystal nickel-iron-manganese-based positive electrode material, comprising the following steps:

[0009] S1. Add a precipitant and a complexing agent to a solution of a stoichiometric ratio of a manganese salt, a nickel salt, an iron salt and an M salt under a protective atmosphere, and perform a coprecipitation reaction and then treat to obtain a hydroxide precursor;

[0010] S2. The hydroxide precursor is mixed with a sodium source, a boron source flux and a strontium source flux by ball milling, and then sintered in three stages under an oxygen atmosphere to obtain a double flux-modified single crystal nickel-iron-manganese-based positive electrode material.

[0011] In one embodiment, in step S1, the M salt is one or more of soluble sulfates, oxalates, acetates, nitrates or chlorides of Mg, Al, Ti, Zn, Zr, Cu, Nb, W, and Mo.

[0012] In one embodiment, in step S2, the boron source flux is H 2 BO 3 , B 2 O 3 , BN, Na 2 BO 3 or B.I. 3 One or more of; the strontium source flux is SrCO 3 , SrC 2 O 4 、Sr[(NO) 3 ] 2 、Sr(OH) 2 、SrCl 2 , SrBr 2 and SrI 2One or more of .

[0013] In one embodiment, the molar ratio of the metal element in the hydroxide precursor, Na in the sodium source, B in the boron source flux and Sr in the strontium source flux is 1:(0.9-1.05):(0.001-0.1):(0.001-0.1).

[0014] In one embodiment, the step S2 comprises:

[0015] The oxygen atmosphere contains more than 50% oxygen, water and CO 2 The sum of the contents is less than 0.1%;

[0016] The three-stage sintering includes pre-calcination, secondary calcination and high-temperature calcination;

[0017] The pre-calcination is to increase the temperature from room temperature to 300-600°C at a heating rate of 1-10°C / min for 4-10h;

[0018] The secondary calcination is to heat the material to 700-800°C at a heating rate of 1-10°C / min and calcine for 4-10h;

[0019] The high temperature calcination is to increase the temperature to 800-950° C. at a heating rate of 1-10° C. / min and sinter for 8-20 hours.

[0020] The present invention also provides a positive electrode plate, which includes a current collector and an active layer located on the surface of the current collector, and the active layer includes the above-mentioned double flux modified single crystal nickel-iron-manganese-based positive electrode material.

[0021] The present invention also provides a sodium ion battery, which comprises the above-mentioned positive electrode plate.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] (1) The double flux modified single crystal nickel-iron-manganese-based positive electrode material of the present invention has a B having a very small ion radius. 3+ Entering the octahedral vacancy of the transition metal layer, Sr, which has a larger ionic radius than sodium ions, 2+ Ions are doped into the sodium layer in the material lattice, allowing the material to maintain its original discharge capacity and improve cycle stability. In the voltage range of 2-4.0V, the discharge capacity of the material at a current rate of 0.1C can reach 138.24mAh g -1 ; In the voltage range of 2-4.0V, the capacity retention rate of the material is still 90.83% after 50 cycles at a current rate of 1C.

[0024] The preparation method of the double flux modified single crystal nickel-iron-manganese-based positive electrode material of the present invention comprises the steps of co-precipitation, dynamic mixing of raw materials and high-temperature sintering, and the flux has strong oxidizing property and electron affinity in the low-temperature melting state, and can undergo redox reaction with the main substance, absorb electrons of other molecules, and make the distance between molecules smaller, thereby changing the chemical state of the molecule, making it easier to transfer or flow at high temperature, reducing the melting point of the substance, accelerating the reaction, promoting particle dispersion, and finally obtaining a single crystal structure, that is, using Sr source and B source flux to realize controllable preparation of single crystal nickel-iron-manganese-based positive electrode material, and the raw materials are easy to obtain, the synthesis method is simple, easy to operate, the synthesis cycle is short, and it is easy to realize industrial production; and the battery prepared by using the positive electrode material is safe, effective, economical and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0026] Figure 1 The microstructure diagram and synthesis principle schematic diagram of the double flux-modified single crystal nickel-iron-manganese-based positive electrode material provided by the present invention; wherein Figure (a) shows the microstructure change of the flux-modified positive electrode material, and Figure (b) is a schematic diagram of the synthesis principle;

[0027] Figure 2 The SEM image and EDS surface scan image of the double flux modified single crystal nickel-iron-manganese-based positive electrode material prepared in Example 1 of the present invention, wherein Figures (a) and (b) are SEM images, and Figure (c) is an EDS spectrum of the material;

[0028] Figure 3 XRD patterns of nickel-iron-manganese-based positive electrode materials prepared in Example 1 and Comparative Example 1 of the present invention, wherein (a) is the double flux-modified single crystal material prepared in Example 1, and (b) is the polycrystalline material prepared in Comparative Example 1;

[0029] Figure 4 The charge and discharge curves of the double flux modified single crystal nickel-iron-manganese-based positive electrode material prepared in Example 1 of the present invention and the polycrystalline material prepared in Comparative Example 1 at a voltage range of 2-4.0V and a current rate of 0.1C;

[0030] Figure 5 The cycle performance of the double flux modified single crystal nickel-iron-manganese based positive electrode material prepared in Example 1 of the present invention and the polycrystalline material prepared in Comparative Example 1 at a current rate of 1C in the voltage range of 2-4.0V;

[0031] Figure 6This is a SEM image of the polycrystalline positive electrode material prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0032] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0033] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0034] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0035] In order to improve the cycle stability and specific capacity of the positive electrode material of sodium ion battery, the inventors of the present application modified the nickel-iron-manganese-based material by using a double solvent, doped in the Na site and transition metal layer structure, and obtained a single crystal nickel-iron-manganese-based positive electrode material, whose chemical formula is: [Na 1-2z Sr z ](Ni a Fe b Mn c M d ) 1-y B y O 2 , wherein M is one or more of Mg, Al, Ti, Zn, Zr, Cu, Nb, W, and Mo, 0<y≤0.1, 0<z≤0.05, and the values ​​of a, b, c, and d depend on the charge balance. The single crystal nickel-iron-manganese-based positive electrode material is an irregular polyhedron, and the particles are evenly dispersed and have a particle size of 2 to 5 μm. Figure 1 As shown in (a), after modification by adding a co-solvent, the positive electrode material appears in a granular form.

[0036] In the present invention, the metal ions in the solvent are doped into the sodium sites of the sodium layer of the nickel-iron-manganese positive electrode material and the octahedral vacancies between the transition metal layers. The principle diagram is as follows: Figure 1 (b) is shown in detail: B is light in mass and has an ionic radius of only 0.27 3+ Inserted into the crystal structure, coordinated with oxygen atoms in a layered structure, stabilized the transition metal layer structure, and inhibited the slip of the transition metal layer during the sodium ion extraction process. The Sr ion radius is slightly larger than the sodium ion radius. 2+ Doping into the sodium layer of the positive electrode material broadens the sodium ion transmission path, improving the material stability while ensuring Na +It can diffuse normally, so that the material maintains the original discharge capacity and improves the cycle stability. It is also the doping of B and Sr that makes the sodium layer spacing The interlayer spacing of transition metal oxides is

[0037] The embodiment of the present application also provides a method for preparing the above-mentioned double flux modified single crystal nickel-iron-manganese-based positive electrode material, comprising the following steps:

[0038] S1. Add a precipitant and a complexing agent to a solution of a stoichiometric ratio of a manganese salt, a nickel salt, an iron salt and an M salt under a protective atmosphere, and perform a coprecipitation reaction and then treat to obtain a hydroxide precursor;

[0039] S2. The hydroxide precursor is mixed with a sodium source, a boron source flux and a strontium source flux by ball milling, and then sintered in three stages under an oxygen atmosphere to obtain a double flux-modified single crystal nickel-iron-manganese-based positive electrode material.

[0040] As an optional embodiment, in step S1, the manganese salt, nickel salt, and iron salt are one or more of sulfate, oxalate, acetate, nitrate, or chloride of manganese, nickel, and iron, and the M salt is one or more of soluble sulfate, oxalate, acetate, nitrate, or chloride of Mg, Al, Ti, Zn, Zr, Cu, Nb, W, and Mo; the precipitant is one or more of sodium hydroxide, potassium hydroxide, barium hydroxide, sodium carbonate, and lithium hydroxide; the complexing agent is one or more of ammonia water, ammonium bicarbonate, ethylenediamine, ethylenediaminetetraacetic acid (EDTA), sodium citrate, or oxalic acid; the process parameters of the coprecipitation reaction are: pH is adjusted to 10-12, and the reaction time is 10-30h. After the coprecipitation reaction, the hydroxide precursor is obtained by solid-liquid separation, repeated washing and impurity removal, and drying.

[0041] As an optional embodiment, in step S2, the boron source flux is H 2 BO 3 , B 2 O 3 , BN, Na 2 BO 3 or B.I. 3 One or more of the following, wherein the strontium source flux is SrCO 3 , SrC 2 O 4 、Sr[(NO) 3 ] 2 、Sr(OH) 2 、SrCl 2 , SrBr 2 and SrI 2The above-mentioned solvent forms a molten state during the sintering process, making it easier for the bulk molecules to transfer or move at high temperatures, promoting particle dispersion, accelerating the synthesis of materials, and finally forming a single crystal material; and Sr 2+ , B 3+ The two are successfully doped into the positive electrode material. They are inactive elements and do not participate in the reaction during the charge and discharge process. Doping into the material improves the cycle stability of the material. The content cannot be too high. Too much doping will lead to a decrease in the proportion of active metal elements and a decrease in the capacity of the material. At the same time, too much doping will cause the problem of being unable to be doped into the material, forming impurities.

[0042] As an optional embodiment, the molar ratio of the metal element in the hydroxide precursor, Na in the sodium source, B in the boron source flux and Sr in the strontium source flux is 1:(0.9-1.05):(0.001-0.1):(0.001-0.1).

[0043] As an optional implementation, in step S2, the oxygen atmosphere mainly plays an oxidizing role. The oxygen content during the sintering process is greater than 50%. During the sintering process, the raw material charge thickness is relatively large. If the oxygen content is low, the bottom layer will not be able to be oxidized. Water and CO 2 Will react with the material, in order to avoid the generated material and water and CO 2 Reaction, water and CO in sintering atmosphere 2 The total content is less than 0.1%.

[0044] As an optional embodiment, the sintering process includes pre-calcination, secondary calcination and high-temperature calcination. The specific process parameters are shown in Table 1:

[0045] Table 1 Sintering process parameters

[0046] stage Heating rate (℃ / min) Calcination temperature (℃) Sintering time (h) Pre-calcination 1-10 300-600 4-10 Secondary calcination 1-10 700-800 4-10 High temperature calcination 1-10 800-950 8-20

[0047] In the present invention, the water in the precursor is first removed at 300-600°C, then the sodium ions are introduced into the material lattice at 600-800°C, and then the material is calcined at 800-950°C to obtain B 3+ Octahedral vacancies in the doped transition metal layer, Sr 2+ Dual flux modified single crystal nickel-iron-manganese based cathode material doped at sodium site in sodium layer.

[0048] The embodiment of the present application also provides a positive electrode sheet, which includes a current collector and an active layer located on the surface of the current collector, wherein the active layer includes the above-mentioned double flux modified single crystal nickel-iron-manganese-based positive electrode material. In addition, the above-mentioned electrode sheets can also be assembled to obtain a sodium battery with excellent performance.

[0049] The above introduces the specific implementation methods of the present application. In order to objectively illustrate the technical effects produced by the present application, the following examples and comparative examples will be used for description.

[0050] Example 1

[0051] A double flux modified single crystal nickel-iron-manganese based positive electrode material and a preparation method thereof, comprising the following steps:

[0052] (1) NiSO 4 7H 2 O,FeSO 4 7H 2 O,MnSO 4 ·H 2 O,CuSO 4 Dissolve in deionized water at a molar ratio of 3:2:3:1 to prepare 2 mol L -1 The transition metal ion solution was then added to a continuous stirred tank reactor under nitrogen atmosphere, and 4 mol L -1 NaOH precipitant and 20 wt% NH 3 ·H 2 After the complexing agent O is added, the pH of the solution is kept in the range of 10-11. After sufficient reaction, it is filtered and washed repeatedly to remove impurities. After drying, Ni 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 (OH) 2 Precursor.

[0053] (2) Take 0.99 mol Ni 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 (OH) 2 Precursor and 0.495 mol Na 2 CO 3 、0.005molSrCO 3 and 0.005 mol of B 2 O 3 The ball milling was performed thoroughly, and the oxygen content exceeded 50%, water and CO 2 The content of the total is less than 0.1% in the atmosphere furnace, the temperature is raised to 500℃ at 5℃ / min, pre-sintered for 4h, then raised to 750℃ for sintering for 4h, and finally raised to 870℃ for 12h, and the chemical formula is [Na 0.99 Sr 0.005 ][Ni 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 ]0.99 B 0.01 O 2 Dual flux modified single crystal nickel iron manganese acid based positive electrode active material.

[0054] Example 2

[0055] A method for preparing a dual-site metal ion-doped sodium nickel iron manganese oxide positive electrode material comprises the following steps:

[0056] (1) NiSO 4 7H 2 O,FeSO 4 7H 2 O,MnSO 4 ·H 2 O, ZnSO 4 Dissolve in deionized water at a molar ratio of 3:2:3:1 to prepare 2 mol L -1 The transition metal ion solution was then added to a continuous stirred tank reactor under nitrogen atmosphere, and 4 mol L -1 NaOH precipitant and 20 wt% NH 3 ·H 2 After the complexing agent O is added, the pH of the solution is kept in the range of 10-11. After sufficient reaction, it is filtered and washed repeatedly to remove impurities. After drying, Ni 1 / 3 Fe 2 / 9 Mn 1 / 3 Zn 1 / 9 (OH) 2 Precursor.

[0057] (2) Take 0.94 mol Ni 1 / 3 Fe 2 / 9 Mn 1 / 3 Zn 1 / 9 (OH) 2 Precursor and 0.47 mol Na 2 CO 3 、0.06mol SrCO 3 and 0.03 mol of B 2 O 3 The ball milling was performed thoroughly, and the oxygen content exceeded 50%, water and CO 2 The content of the total is less than 0.1% in the atmosphere furnace, the temperature is raised to 500℃ at 5℃ / min, pre-sintered for 4h, then raised to 750℃ and sintered for 4h, and finally raised to 800℃ and kept for 12h, and the chemical formula is [Na 0.94 Sr 0.03 ][Ni 1 / 3 Fe 2 / 9 Mn 1 / 3 Zn 1 / 9 ]0.94 B 0.06 O 2 Dual flux modified single crystal nickel iron manganese acid based positive electrode active material.

[0058] Example 3

[0059] A method for preparing a dual-site metal ion-doped sodium nickel iron manganese oxide positive electrode material comprises the following steps:

[0060] (1) NiSO 4 7H 2 O,FeSO 4 7H 2 O,MnSO 4 ·H 2 O,CuSO 4 Dissolve in deionized water at a molar ratio of 3:2:3:1 to prepare 2 mol L -1 The transition metal ion solution was then added to a continuous stirred tank reactor under nitrogen atmosphere, and 4 mol L -1 NaOH precipitant and 20 wt% NH 3 ·H 2 After the complexing agent O is added, the pH of the solution is kept in the range of 10-11. After sufficient reaction, it is filtered and washed repeatedly to remove impurities. After drying, Ni 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 (OH) 2 Precursor.

[0061] (2) Take 0.99 mol Ni 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 (OH) 2 Precursor and 0.495 mol Na 2 CO 3 、0.001molSrCO 3 and 0.0005 mol of B 2 O 3 The ball milling was performed thoroughly, and the oxygen content exceeded 50%, water and CO 2 The content of the total is less than 0.1% in an atmosphere furnace, the temperature is raised to 500℃ at 5℃ / min, pre-sintered for 4h, then raised to 750℃ for sintering for 4h, and finally raised to 950℃ for 12h to obtain a chemical formula of [Na 0.99 Sr 0.005 ][Ni 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 ]0.99 B 0.01 O 2 Dual flux modified single crystal nickel iron manganese acid based positive electrode active material.

[0062] Example 4

[0063] A method for preparing a dual-site metal ion-doped sodium nickel iron manganese oxide positive electrode material comprises the following steps:

[0064] (1) NiSO 4 7H 2 O,FeSO 4 7H 2 O,MnSO 4 ·H 2 O,CuSO 4 Dissolve in deionized water at a molar ratio of 3:2:3:1 to prepare 2 mol L -1 The transition metal ion solution was then added to a continuous stirred tank reactor under nitrogen atmosphere, and 4 mol L -1 NaOH precipitant and 20 wt% NH 3 ·H 2 After the complexing agent O is added, the pH of the solution is kept in the range of 10-11. After sufficient reaction, it is filtered and washed repeatedly to remove impurities. After drying, Ni 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 (OH) 2 Precursor.

[0065] (2) Take 0.90 mol Ni 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 (OH) 2 Precursor and 0.45 mol Na 2 CO 3 、0.1mol SrCO 3 and 0.05 mol of B 2 O 3 The ball milling was performed thoroughly, and the oxygen content exceeded 50%, water and CO 2 The content of the total is less than 0.1% in the atmosphere furnace, the temperature is raised to 500℃ at 5℃ / min, pre-sintered for 4h, then raised to 750℃ for sintering for 4h, and finally raised to 870℃ for 12h, and the chemical formula is [Na 0.9 Sr 0.05 ][Ni 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 ]0.9 B 0.1 O 2 Dual flux modified single crystal nickel iron manganese acid based positive electrode active material.

[0066] Comparative Example 1

[0067] A method for preparing a polycrystalline sodium nickel iron manganate ternary positive electrode material comprises the following steps:

[0068] (1) NiSO 4 7H 2 O,FeSO 4 7H 2 O,MnSO 4 ·H 2 O,CuSO 4 Dissolve in deionized water at a molar ratio of 3:2:3:1 to prepare 2 mol L -1 The transition metal ion solution was then added to a continuous stirred tank reactor under nitrogen atmosphere, and 4 mol L -1 NaOH precipitant and 20 wt% NH 3 ·H 2 After the complexing agent O is added, the pH of the solution is kept in the range of 10-11. After sufficient reaction, it is filtered and washed repeatedly to remove impurities. After drying, Ni 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 (OH) 2 Precursor.

[0069] (2) Take 1 mol Ni 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 (OH) 2 Precursor and 1 mol Na 2 CO 3 The ball milling was performed thoroughly, and the oxygen content exceeded 50%, water and CO 2 The total content of NaNi is less than 0.1%. The temperature is raised to 500℃ at 5℃ / min in an atmosphere furnace, pre-burned for 4h, and then raised to 870℃ and kept warm for 12h to obtain a chemical formula of NaNi 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 O 2 Polycrystalline nickel-iron-manganese-oxide-based positive electrode active material.

[0070] Comparative Example 2

[0071] A method for preparing a boron-doped nickel-iron-manganese-oxide-based positive electrode material comprises the following steps:

[0072] (1) NiSO 4 7H 2 O,FeSO 4 7H 2 O,MnSO 4 ·H 2 O,CuSO 4 Dissolve in deionized water at a molar ratio of 3:2:3:1 to prepare 2 mol L -1 The transition metal ion solution was then added to a continuous stirred tank reactor under nitrogen atmosphere, and 4 mol L -1 NaOH precipitant and 20 wt% NH 3 ·H 2 After the complexing agent O is added, the pH of the solution is kept in the range of 10-11. After sufficient reaction, it is filtered and washed repeatedly to remove impurities. After drying, Ni 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 (OH) 2 Precursor.

[0073] (2) Take 0.99 mol Ni 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 (OH) 2 Precursor and 1 mol Na 2 CO 3 and 0.005 mol of B 2 O 3 The ball milling was performed thoroughly, and the oxygen content exceeded 50%, water and CO 2 The total content of Ni is less than 0.1%. The temperature is raised to 500℃ at 5℃ / min in an atmosphere furnace, pre-burned for 4h, and then raised to 870℃ and kept warm for 12h to obtain a chemical formula of Na[Ni 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 ] 0.99 B 0.01 O 2 Dual flux modified single crystal nickel iron manganese acid based positive electrode active material.

[0074] Comparative Example 3

[0075] A method for preparing a strontium-doped nickel-iron-manganese-acid-based positive electrode material comprises the following steps:

[0076] (1) NiSO 4 7H 2 O,FeSO 4 7H 2O,MnSO 4 ·H 2 O,CuSO 4 Dissolve in deionized water at a molar ratio of 3:2:3:1 to prepare 2 mol L -1 The transition metal ion solution was then added to a continuous stirred tank reactor under nitrogen atmosphere, and 4 mol L -1 NaOH precipitant and 20 wt% NH 3 ·H 2 After the complexing agent O is added, the pH of the solution is kept in the range of 10-11. After sufficient reaction, it is filtered and washed repeatedly to remove impurities. After drying, Ni 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 (OH) 2 Precursor.

[0077] (2) Take 1 mol Ni 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 (OH) 2 The precursor and 0.49 mol Na 2 CO 3 and 0.01 mol of SrCO 3 The ball milling was performed thoroughly, and the oxygen content exceeded 50%, water and CO 2 The content of the total is less than 0.1% in an atmosphere furnace, the temperature is raised to 500℃ at 5℃ / min, pre-burned for 4h, and then heated to 870℃ and kept warm for 12h, and the chemical formula is [Na 0.98 Sr 0.01 ]Ni 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 O 2 Dual flux modified single crystal nickel iron manganese acid based positive electrode active material.

[0078] Spectral analysis

[0079] The double flux modified single crystal nickel-iron-manganese-based positive electrode material obtained in the embodiment was subjected to SEM, EDSHE XRD spectrum analysis. Taking the positive electrode materials obtained in Example 1 and Comparative Example 1 as examples, Figure 2 [Na 0.99 Sr 0.005 ][Ni 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 ] 0.99 B0.01 O 2 SEM and EDS spectra of the positive electrode material, Figure 2 From the SEM image of (a), it can be seen that the material structure is a single crystal structure, and the particle size is about 3μm. Figure 2 (b) The EDS spectrum shows that Sr and B elements are evenly distributed in the material, indicating that Sr 2+ With B 3+ Successfully enter the material lattice; Figure 3 for [Na 0.99 Sr 0.005 ][Ni 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 ] 0.99 B 0.01 O 2 XRD refinement diagram of the positive electrode material. All peak shapes correspond to the standard card. Sr 2+ Occupies the sodium position, B 3+ Occupies the transition metal layer, and the sodium interlayer spacing of the material is The interlayer spacing of transition metals is Figure 6 The polycrystalline NaNi prepared in Comparative Example 1 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 O 2 XRD refinement of the material, all peaks correspond to the standard card, proving that NaNi was successfully synthesized 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 Positive electrode material, calculated by refinement results, the sodium interlayer spacing of the material is Transition metal oxide layer

[0080] Electrical performance analysis

[0081] Battery assembly: Weigh 0.2000g of the positive electrode material prepared in the above embodiment or comparative example, add 0.0250g of conductive carbon black as a conductive agent and 0.0250g of PVDF (polyvinylidene fluoride) as a binder, mix well and apply on aluminum foil to make a positive electrode sheet, in a vacuum glove box, use a metal sodium sheet as the negative electrode, the battery separator is a Whatman GF / D glass fiber separator, and the electrolyte is 1mol / L NaClO 4 (EC: DMC = 1: 1 (volume ratio) + 5% FEC), assembled into a CR2025 button cell. Electrochemical performance tests were conducted in the range of 2-4.0V, and the results are shown in Table 2. Taking Example 1 and Comparative Example 1 as an example for comparison, the comparison results are shown in Table 2. Figure 4 , 5 shown.

[0082] Table 2 Battery electrical performance test results corresponding to the positive electrode materials obtained in the examples and comparative examples

[0083]

[0084] Depend on Figure 4 , 5 It can be seen that compared with the NaNi prepared in Comparative Example 1 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 O 2 Materials, dual-site metal ion doping can stabilize the sodium layer and the transition metal layer at the same time. Transition metal layer doping can enhance the binding ability with oxygen and inhibit the slip of the transition metal layer during the sodium ion deintercalation process. Sodium layer doping can broaden the transmission path of sodium ions, while improving the stability of the material to ensure Na + It can diffuse normally, allowing the material to maintain its original discharge specific capacity and improve cycle stability.

[0085] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the scope of protection of the present invention.

Claims

1. A double flux modified single crystal nickel-iron-manganese based positive electrode material, characterized in that: The chemical formula of the single crystal nickel-iron-manganese-based positive electrode material is: [Na 1-2z Sr z ](Ni a Fe b Mn c M d ) 1-y B y O2, wherein M is one or more of Mg, Al, Ti, Zn, Zr, Cu, Nb, W, Mo, 0<y≤0.1, 0<z≤0.05, and the values ​​of a, b, c, d depend on the charge balance.

2. The double flux modified single crystal nickel-iron-manganese based positive electrode material according to claim 1, characterized in that: The single crystal nickel-iron-manganese-based positive electrode material is an irregular polyhedron, the particles are evenly dispersed, and the particle size is 2 to 5 μm; In the crystal structure of the double flux modified single crystal nickel-iron-manganese-based positive electrode material, the sodium interlayer spacing is The interlayer spacing of transition metal oxides is 3. The double flux modified single crystal nickel-iron-manganese based positive electrode material according to claim 1, characterized in that: The metal ions in the co-solvent are doped into the sodium sites of the sodium layer of the nickel-iron-manganese positive electrode material and the octahedral vacancies between the transition metal layers thereof.

4. The method for preparing a double flux modified single crystal nickel-iron-manganese-based positive electrode material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Add a precipitant and a complexing agent to a solution of a stoichiometric ratio of a manganese salt, a nickel salt, an iron salt and an M salt under a protective atmosphere, and perform a coprecipitation reaction and then treat to obtain a hydroxide precursor; S2. The hydroxide precursor is mixed with a sodium source, a boron source flux and a strontium source flux by ball milling, and then sintered in three stages under an oxygen atmosphere to obtain a double flux-modified single crystal nickel-iron-manganese-based positive electrode material.

5. The method for preparing the double flux modified single crystal nickel-iron-manganese based positive electrode material according to claim 4, characterized in that: In step S1, the M salt is one or more of soluble sulfates, oxalates, acetates, nitrates or chlorides of Mg, Al, Ti, Zn, Zr, Cu, Nb, W, and Mo.

6. The method for preparing the double flux modified single crystal nickel-iron-manganese based positive electrode material according to claim 4, characterized in that: In step S2, the boron source flux is one or more of H2BO3, B2O3, BN, Na2BO3 or BI3; the strontium source flux is one or more of SrCO3, SrC2O4, Sr[(NO)3]2, Sr(OH)2, SrCl2, SrBr2 and SrI2.

7. The method for preparing the double flux modified single crystal nickel-iron-manganese based positive electrode material according to claim 4, characterized in that: The molar ratio of the metal element in the hydroxide precursor, Na in the sodium source, B in the boron source flux and Sr in the strontium source flux is 1:(0.9-1.05):(0.001-0.1):(0.001-0.1).

8. The method for preparing the double flux modified single crystal nickel-iron-manganese based positive electrode material according to claim 4, characterized in that: The step S2 comprises: The oxygen atmosphere has an oxygen content of more than 50% and a water and CO2 content of less than 0.1%; The three-stage sintering includes pre-calcination, secondary calcination and high-temperature calcination; The pre-calcination is to increase the temperature from room temperature to 300-600°C at a heating rate of 1-10°C / min for 4-10h; The secondary calcination is to heat the material to 700-800°C at a heating rate of 1-10°C / min and calcine for 4-10h; The high temperature calcination is to increase the temperature to 800-950° C. at a heating rate of 1-10° C. / min and sinter for 8-20 hours.

9. A positive electrode sheet, characterized in that: The positive electrode plate comprises a current collector and an active layer located on the surface of the current collector, and the active layer comprises the double flux modified single crystal nickel-iron-manganese-based positive electrode material according to any one of claims 1-3.

10. A sodium ion battery, characterized in that: The sodium ion battery comprises the positive electrode sheet according to claim 9.